Barriers to Technology Adoption and Development - Parente, Stephen L.; Prescott, Edward C. (Journal of Political Economy, 1994)
We propose a theory of economic development in which technology adoption and barriers to such adoptions are the focus. The size of these barriers differs across countries and time. The larger these barriers, the greater the investment a firm must make to adopt a more advanced technology. The model is calibrated to the U.S. balanced growth observations and the postwar Japanese development miracle. For this calibrated structure we find that the disparity in technology adoption barriers needed to account for the huge observed income disparity across countries is not implausibly large.